1990
DOI: 10.1159/000174649
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Heart Disease Risk Factors in Women

Abstract: Although men and women share a number of coronary risk factors including age, hypertension, cigarette smoking, diabetes, obesity, plasma lipoprotein concentration, and family history, the overall impact of these factors on the incidence and clinical manifestations of coronary heart disease (CHD) may differ. Additional risk factors which solely impact upon women include the use of oral contraceptives, menopause, and postmenopausal hormones. The impact of psychosocial and behavioral factors on CHD risk in women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
1
4

Year Published

1990
1990
2000
2000

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 39 publications
0
15
1
4
Order By: Relevance
“…Table II shows that myocardial infarction has mortality coefficients that increase with age and reach 31.47 per 100 thousand women in the 45 to 49 age group. Several studies have shown the increasing significance of ischemic heart disease as a cause of morbidity and mortality in women [1][2][3][4]13,19,20 . However, the great majority of these studies are restricted to older, postmenopausal patients, with a discussion about the possibly protective effect of hormone administration in the prevention of ischemic disease in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Table II shows that myocardial infarction has mortality coefficients that increase with age and reach 31.47 per 100 thousand women in the 45 to 49 age group. Several studies have shown the increasing significance of ischemic heart disease as a cause of morbidity and mortality in women [1][2][3][4]13,19,20 . However, the great majority of these studies are restricted to older, postmenopausal patients, with a discussion about the possibly protective effect of hormone administration in the prevention of ischemic disease in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Future study of intervention programs for women with CHD should address each of the following components: (1) participation rates of women, (2) attendance at program sessions, (3) lifestyle change (e.g., reduction of amount of saturated fat consumed or increases in stress management practices), (4) program completion or attrition, (5) psychosocial and quality of life outcomes, (6) physiologic outcomes, and (7) long-term (at least 1 year) follow-up. Within each of these areas, it is important to provide (1) detailed descriptions of assessment methods or the treatment regimen employed, (2) documentation of obstacles by gender (e.g., obstacles for women to participating in an exercise program or changing diet), (3) analyses of gender-specific differences (e.g., in lifestyle change, psychosocial and physiologic outcomes), and (4) psychosocial predictors of change (e.g., in program participation, completion, or long-term maintenance of effects).…”
Section: Discussionmentioning
confidence: 99%
“…Few studies, however, have related behavioral and psyIoronary heart disease (CHD) is the lead-chosocial factors to lifestyle change or linked »ing cause of death in Western culture.1,2 lifestyle change to coronary risk reduction. [5][6][7] The impact of the disease spreads beyond the Rarer still are studies relating lifestyle change suffering of an individual patient. Society also specifically to CHD in women.8 This is not surpays an enormous price.3 Traditional invasive prising, as a large gender gap exists in CHD reapproaches to treatment are expensive.…”
mentioning
confidence: 99%
“…Analysis of risk factors for acute myocar dial infarction in women reveals that the usual factors are associated with cardiovas cular disease are implicated and are re viewed in a recent publication [24], Hyper lipidemia [10, 20. 25.…”
Section: Risk Factorsmentioning
confidence: 99%